2021
DOI: 10.1021/acs.inorgchem.1c01771
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Microporous M-HOFs Based on an Octahedral Rhenium Cluster with Benzimidazole

Abstract: Substitution of apical halide ligands in [{Re6Sei 8}­Xa 6]3– (X = Cl, Br) by benzimidazole (bimzH) accompanied by a self-assembly process leads to the formation of microporous Re6-based hydrogen-bonded organic frameworks (Re6-HOFs) constructed on N–H···X hydrogen bonds and π–π-stacking interactions between bimzH ligands. Re6-HOFs demonstrate sorption properties with a Brunauer–Emmett–Teller surface area of up to 443 m2 g–1 and luminescence with a quantum yield and an emission lifetime of up to 0.16 and 16 μs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Especially, when metal complexes act as building units in SOFs, the metals may endow SOFs with additional functions, such as luminescence and magnetism. 28,29 For instance, Wang et al reported a few SOFs with Dy( iii ) complexes as the building units. These SOFs show the off/on magnetic conversion behavior as single-ion magnets because of the large single-ion magnetic anisotropy of Dy( iii ) ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, when metal complexes act as building units in SOFs, the metals may endow SOFs with additional functions, such as luminescence and magnetism. 28,29 For instance, Wang et al reported a few SOFs with Dy( iii ) complexes as the building units. These SOFs show the off/on magnetic conversion behavior as single-ion magnets because of the large single-ion magnetic anisotropy of Dy( iii ) ions.…”
Section: Introductionmentioning
confidence: 99%
“…SOFs, the metals may endow SOFs with additional functions, such as luminescence and magnetism. 28,29 For instance, Wang et al reported a few SOFs with Dy(III) complexes as the building units. These SOFs show the off/on magnetic conversion…”
mentioning
confidence: 99%
“…Hydrogen-bonded metal-organic frameworks (H-MOFs) have a metal complex as a building unit, in which they are connected through H-bonding. [1][2][3][4][5][6][7][8][9][10][11] They have been applied to the molecular porous materials like the typical MOFs [12][13][14] and covalent organic frameworks (COFs). 15,16 The magnitude of Hbonding determines the flexibility between units and can be controlled via the electrostatic interactions between the donor and acceptor moieties.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few examples of such clusters with N-heterocyclic ligands are reported and only three of them are structurally characterized [40,41]. On the contrary, a fairly large number of complexes with coordinated heterocycles have been obtained in the case of rhenium clusters [42,43], indicating that N-heterocyclic ligands can preserve their useful properties upon coordination to metal centers. For example, clusters [{Re 6 Q 8 }(btrz) 6 ] 4-(Q = S, Se; btrz is benzotriazolate) similar to pure btrzH are able to bind directly to DNA [42].…”
Section: Introductionmentioning
confidence: 99%